Bio-efficacy impact of botanical powders against Callosobruchus chinensis infesting different stored pulses: A review - Tumma Mounika; Peddi Naga Harsha Vardhan; Tapan Kumar Hath; Akhila Badavath (Environment Conservation Journal)
After harvest, pulses are usually stored in godowns. At the post-harvest level, the bruchid (pulse beetle) has long been responsible for both qualitative and quantitative losses. Both in the field and during storage, the bug targets the crop. However, storage circumstances are where insect attacks are more common. Fifty to sixty percent of the grains may be harmed, even after six months of conventional storage. In extreme infestation situations, the grains become unfit for human eating and the damage might amount to up to 100%. Nowadays, synthetic fumigants and insecticides are frequently used in insect management approaches. Substance safety-related actions could have a lot of detrimental impacts. Insecticides used frequently and carelessly can cause natural imbalances that prevent insects from surviving, aid in their recovery, and cause secondary insect epidemics that leave phytotoxic pesticide residues in food and food. These drawbacks make it challenging for scientists worldwide to advocate for alternate methods of controlling insects. It is a local technology that uses readily available natural resources to manage dangerous insects. Recently, scientists have successfully tested a range of plant crops, including oils and powders, in different parts of the world. Researchers evaluated the efficacy of various natural botanical powders as insecticides against Callosobruchus chinensis in-person while keeping these viewpoints in mind. The goal of this review is to demonstrate how various plant elements, such as leaves, bark, and seeds, benefit ecosystems and assist pulse beetles live longer and have more offspring, which reduces damage and weight loss. It can be used in place of conventional pest control techniques.